Pengaruh Kepemimpinan Transformasional terhadap Kinerja Pegawai dengan Motivasi Kerja sebagai Variabel Intervening pada Dinas Kependudukan dan Pencatatan Sipil Kota Jambi - Anil Farhan Ramadan; Sumarni Sumarni; Dwi Kurniawan (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to investigate the influence of transformational leadership on employee performance with work motivation as an intervening variable at the Civil Registration and Population Office of Jambi City. The analysis method used is quantitative. The population and sample in this study are all employees at the Civil Registration and Population Office of Jambi City, totaling 89 respondents, using a saturated sampling technique. The statistical analysis used is structural equation modeling (SEM) with the SmartPLS 4.0.0 program. The results show a positive and significant influence of transformational leadership on employee performance with work motivation as an intervening variable at the Civil Registration and Population Office of Jambi City. The recommendations from this study include fostering open communication between superiors and subordinates for employee performance, enhancing problem-solving methods within the organization for transformational leadership, and granting autonomy to employees in their work for work motivation.or formula.